The Foreigners’ Problems, Needs and Guidelines in Thai Language Communication for Developing Communicative Thai Language Teaching Applications for Foreigners - Maprom, Khankaeo (Journal for Developing the Social and Community, 2025)
Background and Aims: This research aimed to investigate the current problems, needs, and development guidelines for a communication Thai language teaching application for foreigners. Mothodology: This research was the Phase 1 of the Research and Development. The target group consisted of 50 foreigners traveling and residing in Thailand, selected through purposive sampling. The research instruments included questionnaires and interview forms with validated content validity (IOC 0.50–1.00) and reliability (0.70–0.90). Data were analyzed using percentage, mean (), standard deviation (S.D.), and t-test. Result: 1. Communication Problems: Overall communication problems were rated at a high level (=4.34). The most significant issue was listening (=4.60), followed by speaking (=4.49), primarily due to limitations in vocabulary and sentence construction. Reading, writing, and overall communication were also rated at high problem levels. These issues reflect the unique characteristics of the Thai language, which is globally recognized as difficult due to its complex tonal system and word structures. Comparative analysis revealed that foreign tourists experienced significantly higher overall communication problems than long-term residents. Specifically, residents living in Thailand for more than 6 years (12 participants, 16.00%) reported a moderate level of communication difficulty (=3.48). 2. Needs Assessment: The target group expressed the highest level of need for a skill development application (76%, =4.56, S.D. = 0.56). They preferred learning with bilingual Thai instructors (Thai-English) (xˉ=4.70, S.D. = 0.49). Desired content focused on 8 practical contexts: greetings, self-introductions, asking for help, public transportation, shopping, ordering food, making appointments, and communication in educational institutions., and 3. Development Guidelines: The application should be developed based on Mobile Learning (m-Learning) and Interaction Design (IxD) principles. It must support both iOS and Android to facilitate "Anywhere, anytime" learning, emphasizing accessibility and portability. Key features should include context-aware and micro-learning approaches, utilizing audio clips for ear training to overcome linguistic contrasts. Specialized features such as minimal pair distinctions, speed control, and visual waveforms are recommended to assist with consonant and cluster sound differentiation. Furthermore, the application should integrate visual-based learning and authentic learning by incorporating regional Thai dialects to align with the lifestyles of foreigners residing in various regions of Thailand. Conclusion: Listening Difficulties and Interlanguage Challenges. The study reveals that international tourists and residents in Thailand face the highest level of difficulty in Thai language listening comprehension (=4.60). The primary obstacles are a lack of vocabulary knowledge and the inability to distinguish Thai tonal variations. These issues are not necessarily attributed to the learners’ deficiencies but rather to the Interlanguage phenomenon, where learners are constrained by the phonological structures of their native language (L1). According to Contrastive Analysis Theory, the degree of linguistic distance between the L1 and the target language (L2) directly correlates with the severity of learning difficulties. Demand for Mobile Application Development: There is a critical demand for the development of a Thai language learning application, rated at the highest level. The findings indicate that: Content: Users prioritize Thai for communication across eight specific contexts. Instructional Style: Learners prefer bilingual instruction (Thai and English) delivered by native Thai instructors. Platform: A mobile-based application was the most preferred medium for learning. Design Principles and Recommendations: Participants suggested that the application should align with Mobile Learning (m-Learning) and Interaction Design (IxD) principles. Key recommendations include: Integration of contemporary vocabulary and authentic daily life expressions. Implementation of Authentic Learning by incorporating regional Thai dialects. Contextualizing content to match the actual lifestyles of expatriates living in diverse regions across Thailand.